2021
DOI: 10.1038/s41558-021-01047-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures that sterilize males better match global species distributions than lethal temperatures

Abstract: This is a repository copy of Temperatures that sterilize males better match global species distributions than lethal temperatures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 26 publications
8
141
0
Order By: Relevance
“…Typical estimates of thermal sensitivity describe the temperatures at which individuals fail to maintain basic physiological functions such as controlled locomotion and respiration (Lutterschmidt & Hutchison, 1997). Approaches to predict organismal responses relying exclusively on such measures are however bound to neglect a variety of sublethal effects that will arise at less extreme temperatures, the most important being reductions in fertility (Angilletta, 2009;Chirgwin et al, 2021;Hoffmann et al, 2013;Kellermann & van Heerwaarden, 2019;Parratt et al, 2021;Walsh et al, 2019). Indeed, already a slight decrease in fertility can have dramatic effects on population viability (Degioanni et al, 2019) and thermal plasticity in reproductive traits affecting fertility is widespread (Dell et al, 2011;Deutsch et al, 2008;Frazier et al, 2006) and often observable at a significantly lower temperature threshold than responses in viability (Angilletta, 2009;Gerking & Lee, 1983;Hoffmann, 2010;Loisel et al, 2019;van Heerwaarden & Sgrò, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical estimates of thermal sensitivity describe the temperatures at which individuals fail to maintain basic physiological functions such as controlled locomotion and respiration (Lutterschmidt & Hutchison, 1997). Approaches to predict organismal responses relying exclusively on such measures are however bound to neglect a variety of sublethal effects that will arise at less extreme temperatures, the most important being reductions in fertility (Angilletta, 2009;Chirgwin et al, 2021;Hoffmann et al, 2013;Kellermann & van Heerwaarden, 2019;Parratt et al, 2021;Walsh et al, 2019). Indeed, already a slight decrease in fertility can have dramatic effects on population viability (Degioanni et al, 2019) and thermal plasticity in reproductive traits affecting fertility is widespread (Dell et al, 2011;Deutsch et al, 2008;Frazier et al, 2006) and often observable at a significantly lower temperature threshold than responses in viability (Angilletta, 2009;Gerking & Lee, 1983;Hoffmann, 2010;Loisel et al, 2019;van Heerwaarden & Sgrò, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, already a slight decrease in fertility can have dramatic effects on population viability (Degioanni et al, 2019) and thermal plasticity in reproductive traits affecting fertility is widespread (Dell et al, 2011;Deutsch et al, 2008;Frazier et al, 2006) and often observable at a significantly lower temperature threshold than responses in viability (Angilletta, 2009;Gerking & Lee, 1983;Hoffmann, 2010;Loisel et al, 2019;van Heerwaarden & Sgrò, 2021). Hence, it is crucial to incorporate estimates of the thermal sensitivity of fertility (from hereon: TSF) into predictions of population persistence (Angilletta, 2009;Parratt et al, 2021;Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use fertility to mean the ability to produce offspring, the direct opposite of sterility. We use this definition because complete sterility has the potential to be extremely important in a warming world (Parratt et al, 2021 ; Walsh et al, 2019 ; van Heerwaarden & Sgrò, 2021 ). Heat‐induced sterility occurs across diverse taxa including crops (Matsui et al, 1997 ) and livestock (Karaca et al, 2002 ), so species where fertility is lost at temperatures far below the lethal limit may represent both a major economic and conservation concern (Walsh et al, 2019 ) with potentially worrying implications for humanity's resilience against climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility loss is generally sex‐specific, with males often more sensitive to fertility loss than females (Iossa, 2019 ; Sales et al, 2018 ; Walsh et al, 2021 ; Zwoinska et al, 2020 ). Recent work has found that the highest temperatures Drosophila species are found at worldwide is strongly correlated to laboratory measurements of their lethal temperature, or the temperature at which males lose fertility, whichever is the lower (Parratt et al, 2021 ; van Heerwaarden & Sgrò, 2021 ). This suggests that species distributions may often be restricted by their upper thermal limits to fertility in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation